2007
DOI: 10.1085/jgp.200709812
|View full text |Cite
|
Sign up to set email alerts
|

Phosducin Regulates the Expression of Transducin βγ Subunits in Rod Photoreceptors and Does Not Contribute to Phototransduction Adaptation

Abstract: For over a decade, phosducin's interaction with the βγ subunits of the G protein, transducin, has been thought to contribute to light adaptation by dynamically controlling the amount of transducin heterotrimer available for activation by photoexcited rhodopsin. In this study we directly tested this hypothesis by characterizing the dark- and light-adapted response properties of phosducin knockout (Pd−/−) rods. Pd−/− rods were notably less sensitive to light than wild-type (WT) rods. The gain of transduction, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 52 publications
(91 reference statements)
7
37
0
Order By: Relevance
“…G␥ 1 contains specific ubiquitination sites tagging G␤ 1 ␥ 1 for proteolysis by the 26S proteasome (Obin et al, 2002). This ubiquitination has been shown to be regulated by phosducin in vitro (Obin et al, 2002), and phosducin knock-out results in ϳ36% loss of G␤ 1 ␥ 1 in rods (Sokolov et al, 2004;Krispel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…G␥ 1 contains specific ubiquitination sites tagging G␤ 1 ␥ 1 for proteolysis by the 26S proteasome (Obin et al, 2002). This ubiquitination has been shown to be regulated by phosducin in vitro (Obin et al, 2002), and phosducin knock-out results in ϳ36% loss of G␤ 1 ␥ 1 in rods (Sokolov et al, 2004;Krispel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…By interacting with transducin, phosducin can curb rod visual signalling. [56,83,84] However, single cell experiments based on suction electrode recordings have revealed that the above-mentioned effect on rod light adaptation is not influenced by the lack of phosducin under moderate light conditions [69]. The facilitation of transducin translocation seems rather to be a matter of light intensity playing a role in brightly illuminated environments.…”
Section: Phosducin's Functions In the Retinamentioning
confidence: 99%
“…The facilitation of transducin translocation seems rather to be a matter of light intensity playing a role in brightly illuminated environments. Yet, the gain of transductionmeasured by the amplification constant-was diminished in Pdc -/-rods compared to wild-type cells in single cell recordings [69]. It has been suggested that, rather than adjusting the availability of transducin heterotrimer and thereby controlling light sensitivity, phosducin exerts longer-term regulatory functions allocating transducin expression levels.…”
Section: Phosducin's Functions In the Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…PhLP1 (often called PhLP) is ubiquitously expressed (15) and is shown to act as a CCT co-factor during the folding of G protein ␤ (16 -20). In contrast, phosducin is expressed predominantly in rod and cone photoreceptors, where it helps maintain high lev-els of and assists in the trafficking of the visual G protein transducin without any known connection to CCT (21)(22)(23). Subgroup II consists of PhLP2A and PhLP2B, which were both discovered in humans (13).…”
mentioning
confidence: 99%